Sleeve Gastrectomy and Roux-en-Y Gastric Bypass Alter the Gut-Brain Communication - L. A. Ballsmider; A. C. Vaughn; M. David; A. Hajnal; P. M. Di Lorenzo; K. Czaja (Neural Plasticity)
This study investigated the anatomical integrity of vagal innervation of the gastrointestinal tract following vertical sleeve gastrectomy (VSG) and Roux-en-Y gastric bypass (RYGB) operations. The retrograde tracer fast blue (FB) was injected into the stomach to label vagal neurons originating from nodose ganglion (NG) and dorsal motor nucleus of the vagus (DMV). Microglia activation was determined by quantifying changes in the fluorescent staining of hindbrain sections against an ionizing calcium adapter binding molecule 1 (Iba1). Reorganization of vagal afferents in the hindbrain was studied by fluorescent staining against isolectin 4 (IB4). The density of Iba1- and IB4-immunoreactivity was analyzed using Nikon Elements software. There was no difference in the number of FB-labeled neurons located in NG and DMV between VSG and VSG-sham rats. RYGB, but not RYGB-sham rats, showed a dramatic reduction in number of FB-labeled neurons located in the NG and DMV. VSG increased, while the RYGB operation decreased, the density of vagal afferents in the nucleus tractus solitarius (NTS). The RYGB operation, but not the VSG procedure, significantly activated microglia in the NTS and DMV. Results of this study show that the RYGB, but not the VSG procedure, triggers microglia activation in vagal structures and remodels gut-brain communication.